The Readability of Reading Text on The English Textbook for XI Grade Students Published by The Ministry of Educational and Cultural Indonesia 2019 - Rr Ajutriesna Lawijanti Indryasari (STKIP PGRI SIDOARJO, 2019)
This research sought to explore the readability of textbook for use by Senior High School Grade XI Semester 1 student in the year 2019. This research is used descriptive qualitative. It means that reading is about understanding written texts. If reading English text is not interest, vocabularies are hard to understand, the students get difficult to understand the reading passage. The readability level of text is needed to motivate students to be able to build up their interest in reading text. This research investigates the readability level of reading texts in English Textbook Entitled “Bahasa Inggris” for senior high school students grade XI. The method used in this study is descriptive qualitative. The data were gathered through analysis the readability level of the texts used Flesch Reading Ease Formula.